Unraveling the transcriptomic effects of leucine supplementation on muscle growth and performance in basketball athletes - Sinan Wang; Weishuai Guo; Rui Dong (PLoS ONE, 2025)
Leucine has gained recognition as an athletic dietary supplement in recent years due to its various benefits; however, the underlying molecular mechanisms remain unclear. In this study, 20 basketball players were recruited and randomly assigned to two groups. Baseline exercise performance—assessed through a 282-foot sprint, free throws, three-point field goals, and self-rated practice assessments—was measured prior to leucine supplementation. Participants were then given a functional drink containing either leucine (50 mg/kg body weight) or a placebo for 28 days. After supplementation, the same exercise performance metrics were reassessed. Following leucine supplementation, biceps brachii muscle tissue from both groups was collected for transcriptome sequencing and qPCR verification. Our results suggested that leucine supplementation significantly improved 282-foot sprint performance, reducing times from 17.4 ± 0.9 to 16.2 ± 0.9 seconds in the leucine group, compared to minimal changes in the control group (from 17.3 ± 0.9 to 17.1 ± 0.8 seconds; P = 0.034). For other exercise performance metrics, no significant differences were observed (P > 0.05); however, trends toward improvement were noted. Transcriptomic analysis revealed 3,658 differentially expressed genes (DEGs) between the two groups. These DEGs were enriched in pathways related to immune response (P < 0.0001), positive regulation of cytokine production (P < 0.0001), and neutrophil extracellular trap formation (P < 0.0001), among others. Weighted Gene Co-expression Network Analysis (WGCNA) identified a module (turquoise) strongly associated with muscle growth, with DEGs in this module enriched in cytoskeletal pathways in muscle cells. Gene expression changes (α-tubulin, β-tubulin, CK18, CK8, vimentin, cofilin, gelsolin, profilin, MAP1, MAP2, MAP4, E-cadherin, and N-cadherin) were verified by qPCR. In summary, leucine supplementation improved exercise performance, particularly by significantly reducing sprint times and showing trends of improvement in other performance metrics, including three-point field goals, free throws, and self-rated well-being. Identified DEGs enriched in pathways related to immune response, cytokine production, and cell adhesion. WGCNA highlighted a key module associated with muscle growth, enriched in cytoskeletal pathways. qPCR validation confirmed the upregulation of cytoskeleton-related genes, supporting the transcriptomic findings. These results suggest that leucine enhances muscle adaptation by regulating cytoskeletal dynamics, providing molecular insights into its role in improving athletic performance.